The quality of teaching by lecturers in the evaluation of students of the Academy of Physical Education and University of Economics in Katowice - Socha, Paulina (Quality in Sport, 2015)
The aim of the study was to present the expectations of students towards their teachers in the teaching process . Material and methods. The study was conducted using the questionnaire method among students of Physical Education and the University of Economics in Katowice. Assessed the quality of education by using 5-points Likerts scale . Basic results. The most highly valued aspects of the work of lecturers were having practical knowledge, skill and competence of its transmission. Conclusions. The study may serve scholars to align standards and level of education relative to the requirements of the students.